Assessing Occupational Safety Risks And Prevention Strategies Among Ambulance Personnel In The Saudi Red Crescent Authority In Light Of The Objectives Of Vision 2030 (The Review of Diabetic Studies, 2025)
Background:Saudi Arabia’s Vision 2030 represents a transformative national strategy that seeks to diversify the economy, enhance the quality of life, and position the Kingdom as a leading global tourism destination. As visitor numbers rapidly increase through projects such as NEOM, AlUla, and the Red Sea Development, the need for specialized tourist ambulance services becomes critical to ensuring safety, trust, and visitor satisfaction.Aim:This study proposes a comprehensive vision and conceptual framework for managing tourist ambulance services in Saudi Arabia, aligned with the goals of Vision 2030 and its related programs, including the Quality of Life and Health Sector Transformation initiatives.Methods:A qualitative, descriptive, and conceptual framework design was employed. A systematic literature review and document analysis were conducted across databases (PubMed, Scopus, ScienceDirect) and national reports (SRCA, Ministry of Tourism, Vision 2030 portal) from 2015 to 2025. Thematic analysis identified administrative, clinical, and technical domains that collectively define the core components of a sustainable tourist emergency response system.Results:Three interdependent pillars emerged: (1) Administrative and governance frameworks ensuring policy integration and inter-ministerial coordination; (2) Clinical excellence emphasizing multilingual, culturally competent, and patient-centered care; and (3) Technical innovation integrating digital dispatch, GIS, ePCR, and telemedicine technologies. These elements collectively enhance response efficiency, safety, and the visitor experience.Conclusion:The proposed vision emphasizes that tourist ambulance management should be an integrated, data-driven, and visitor-focused system. Implementing this framework will strengthen Saudi Arabia’s international reputation as a safe and reliable destination, directly supporting Vision 2030’s goals of health sector transformation, service excellence, and quality of life.